1-year survival rate of ICU patients undergoing tracheotomy, a low volume hospital experience: 1-letno preživetje bolnikov v EIT po traheotomiji — izkušnja bolnišnice z majhnim številom bolnikov - Mohorko, Janez; Markota, Andrej; Čizmarevič, Bogdan (Acta Medico-Biotechnica, 2021)
Purpose: Many critically ill patients require a tracheotomy during their ICU (Intensive Care Unit) stay. The aim of this study was to determine how many patients that undergo this procedure survive the hospital stay and are alive 1 year after the procedure.Methods: We retrospectively included 144 patients who had tracheotomies during their ICU stay at the UMC (University Medical Centre) Maribor in 2015 and compared the survival between patients hospitalized in the MICU (Medical Intensive Care Unit) and SICU (Surgical Intensive care unit).Results: This study showed that survival after tracheotomy in critically ill patients is low. Only 9.7% of all patients live without a tracheostomy after 1 year. The differences that were statistically significant between the MICU and SICU were observed only after the discharge from the ICU, with more people survivingthe MICU stay.Conclusions: There is little information involving 1-year survival rates of patients undergoing tracheotomies. We conclude that more studies regarding this issue need to be conducted.
Keywords: tracheotomy; 1-year survival